"Palinomorfos de la Formación Los Espejos (Ludloviano medio-tardío) de Aguada de Los Azulejitos, Precordillera central, San Juan, Argentina" (Ameghiniana, 2014)
"Two prasinophyte and 36 aeritareh taxa fromthe lower mernber of the Los Espejos Formation are presented herein. Duoernausphaera oa Loeblieh andWieancler and Pterospennella uerrucaboia Loeblieh and Wicander of lower Devonian age in USA are mentionedfor the first time in Argentina. Domasia rochesterensis Thusu is reported frorn the Wenloekian ofEnglancl, Sweclen and Cariada, and D0111asia canadensis Thusu from the Wenloekian of Canada. A eombination:Paíacolntstichosplureridiuni siluricum (Pothe de Baldis) nov. combo is proposed herein. The eosmopolitanforrns presented here are related to those present in Laurentian Devonian North American and DevonianCanadian sed iments, Perigondwanie Ludlovian-Emsian from Spain, Upper Ordovician from Franceand Wenlockian from Great Britain. This mieroflora is al so related to Australian Upper Devonian ones."